Absolute Configuration from Different Multifragmentation Pathways in Light‐Induced Coulomb Explosion Imaging. Issue 16 (14th June 2016) - Pitzer, Martin; Kastirke, Gregor; Kunitski, Maksim; Jahnke, Till; Bauer, Tobias; Goihl, Christoph; Trinter, Florian; Schober, Carl; Henrichs, Kevin; Becht, Jasper; Zeller, Stefan; Gassert, Helena; et al.
Abstract: The absolute configuration of individual small molecules in the gas phase can be determined directly by light‐induced Coulomb explosion imaging (CEI). Herein, this approach is demonstrated for ionization with a single X‐ray photon from a synchrotron light source, leading to enhanced efficiency and faster fragmentation as compared to previous experiments with a femtosecond laser. In addition, it is shown that even incomplete fragmentation pathways of individual molecules from a racemic CHBrClF sample can give access to the absolute configuration in CEI. This leads to a significant increase of the applicability of the method as compared to the previously reported complete break‐up into atomic ions and can pave the way for routine stereochemical analysis of larger chiral molecules by light‐induced CEI. Abstract : Big bang for the absolute configuration ! Light‐induced Coulomb explosions can image the absolute configuration of small molecules in the gas phase. It is shown that even partial fragmentation displays the signature of handedness—an important step for the application of Coulomb explosion imaging to larger molecules.